A Review on Biomedical Titanium Alloys: Recent Progress and Prospect. Issue 4 (20th March 2019) - Zhang, Lai‐Chang; Chen, Liang‐Yu
Abstract : Compared with stainless steel and Co–Cr‐based alloys, Ti and its alloys are widely used as biomedical implants due to many fascinating properties, such as superior mechanical properties, strong corrosion resistance, and excellent biocompatibility. After briefly introducing several most commonly used biomedical materials, this article reviews the recent development in Ti alloys and their biomedical applications, especially the low‐modulus β ‐type Ti alloys and their design methods. This review also systemically investigates the recently attractive progress in preparation of biomedical Ti alloys, including additive manufacturing, porous powder metallurgy, and severe plastic deformation, applied in the manufacturing and the influenced microstructures and properties. Nevertheless, there are still some problems with the long‐term performance of Ti alloys, and therefore several surface modification methods are reviewed to further improve their biological activity, wear resistance, and corrosion resistance. Finally, the biocompatibility of Ti and its alloys is concluded. Summarizing the findings from literature, future prediction is also conducted. Abstract : This paper reviews the recent development in Ti alloys and their biomedical applications, including additive manufacturing, porous powder metallurgy, and severe plastic deformation applied in the manufacturing and the influenced microstructures and properties. Nevertheless, some problems exist in long‐term performance of Ti alloys. Hence, several surface modification methods are reviewed to improve their biological activity, wear resistance, and corrosion resistance.